Travestis and transsexual women: who are at higher risk for sexually transmitted infections? - Paulie Marcelly Ribeiro dos Santos; Kamila Cardoso dos Santos; Larissa Silva Magalhães; Brunna Rodrigues de Oliveira; Megmar Aparecida dos Santos Carneiro; Márcia Maria de Souza; Karlla Antonieta Amorim Caetano; Leonora Rezende Pacheco; Sheila Araújo Teles (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objective: To compare social characteristics, risk behaviors, and sexually transmitted infections among travestis and transsexual women. Methodology: A cross-sectional study was carried out in three cities in Goiás, Central Brazil. Trans women were interviewed on sociodemographic characteristics, discrimination, prejudice, sexual behavior, illicit drugs, and previous testing for HIV and syphilis between April 2018 and August 2019. Results: A total of 166 travestis and 249 transsexual women were investigated. Although sexual, physical, and verbal violence were common to both groups, sexual behavior, use of illicit drugs, prison, and previous positive HIV and syphilis testing were more frequent among travestis than in transsexual women. Conclusion: The present findings confirm that Brazilian travestis are at greater risk for sexually transmitted infections (STI), indicating that health services should take this imbalance into account in terms of health intervention proportions.